THE IMPORTANCE OF THE REALISATION OF THE RIGHT OF THE CHILD TO PARTICIPATE IN CHILDREN’S DAY CARE CENTRES - Raudeliūnaitė, Rita; Gudžinskienė, Vida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The aim of the study is to reveal the importance of the realisation of the right of the child to participate in children’s day care centres based on the experience of social pedagogues and social workers. Qualitative research was chosen for the study by using the method of semi-structured interview. 11 employees, who work in children’s day care centres in different Lithuanian regions, participated in the study. The study revealed the importance of the implementation of the right of the child to participate to the child, employees, the quality of provided socio-educational services and the continuity of the implementation of this right when cooperating with the family of the child successfully. The importance to the child should be associated with the strengthening of his/her dignity, self-esteem, self-confidence, the ensuring of his better well-being and emotional security; the self-realisation of the child, his/her problem solving, communication, cooperation, activity planning and organizational skills improve, the child develops responsibility and autonomy when taking and realising decisions. The importance to employees should be associated with the better knowledge of the child and understanding of his/her situation, satisfaction of his/her needs, the formation of the relationship with the child based on cooperation. The importance to the quality of provided services should be associated with activities, which meet the needs of the child, the guarantee of a favourable socio-educational environment in children’s day care centres, the opportunity for the child to influence the planning and organization of activities in children’s day care centres. The cooperation with the family of the child guarantees the continuity of the implementation of the right of the child to participate, because parents understand the importance of this right to the well-being of the child and create possibilities for its implementation.